Smart virtual parking mobile application. Issue 1 (2nd January 2018) - Aldayan, Yasser; Alghamdi, Abdulkareem; Alotaiby, Khalid; Saudagar, Abdul Khader Jilani
Abstract: Students drive to the university every day and they often struggle with finding a car parking space. This can be challenging and wasting a lot of students' time. To solve this problem this project develops a virtual parking mobile application to meet the student necessity. The students can login to the app and the app will show them which spots are available and which are busy. Students can also reserve a parking spot, and can hold for couple of minutes until they reach the parking spot. This project emulates the parking lot facility through a virtual design to represent a real live parking lot. The result of the actions that will take place on the virtual design will be appearing on the mobile application.